Adoptive cytotoxic T lymphocyte therapy triggers a counter‐regulatory immunosuppressive mechanism via recruitment of myeloid‐derived suppressor cells. Issue 8 (21st October 2013) - Hosoi, Akihiro; Matsushita, Hirokazu; Shimizu, Kanako; Fujii, Shin‐ichiro; Ueha, Satoshi; Abe, Jun; Kurachi, Makoto; Maekawa, Ryuji; Matsushima, Kouji; Kakimi, Kazuhiro
<x xml:space="preserve">Abstract</x> Complex interactions among multiple cell types contribute to the immunosuppressive milieu of the tumor microenvironment. Using a murine model of adoptive T‐cell immunotherapy (ACT) for B16 melanoma, we investigated the impact of tumor infiltrating cells on this complex regulatory network in the tumor. Transgenic pmel‐1‐specific cytotoxic T lymphocytes (CTLs) were injected intravenously into tumor‐bearing mice and could be detected in the tumor as early as on day 1, peaking on day 3. They produced IFN‐γ, exerted anti‐tumor activity and inhibited tumor growth. However, CTL infiltration into the tumor was accompanied by the accumulation of large numbers of cells, the majority of which were CD11b+Gr1+ myeloid‐derived suppressor cells (MDSCs). Notably, CD11b+Gr1intLy6G−Ly6C+ monocytic MDSCs outnumbered the CTLs by day 5. They produced nitric oxide, arginase I and reactive oxygen species, and inhibited the proliferation of antigen‐specific CD8+ T cells. The anti‐tumor activity of the adoptively‐transferred CTLs and the accumulation of MDSCs both depended on IFN‐γ production on recognition of tumor antigens by the former. In CCR2−/− mice, monocytic MDSCs did not accumulate in the tumor, and inhibition of tumor growth by ACT was improved. Thus, ACT triggered counter‐regulatory immunosuppressive mechanism via recruitment of MDSCs. Our results suggest that strategies to regulate the treatment‐induced recruitment of these MDSCs would improve the efficacy of immunotherapy.